2020
DOI: 10.1101/2020.10.26.20218495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speech cortical activation and connectivity in typically developing children and those with listening difficulties

Abstract: Listening difficulties (LiD) are a widespread but poorly understood form of hearing impairment in people who have normal audiometry. Recent research suggests that childhood LiD are cognitive rather than auditory in origin. We assessed that hypothesis using behavioral testing and fMRI with 43 typically developing children and 42 children with LiD, categorized by caregiver report. The children with LiD had clinically normal hearing. For sentence listening tasks, we found no group differences in fMRI brain cortic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…Children with APD had increased functional connectivity in the left inferior frontal gyrus (Broca’s area) and left posterior middle temporal gyrus; these regions are implicated in language production and comprehension and lexical and semantic processes (Hagoort, 2014; Acheson et al, 2013; Hickok & Poeppel, 2004). Stewart and colleagues (2021) also reported that in the Semantics network, children with APD had stronger functional connectivity in the right parahippocampal gyrus compared to auditory areas such as left Heschl’s gyrus, left middle temporal gyrus (MTG), right superior temporal gyrus (STG), and right planum temporale. Still, they had weaker connections in the left temporal fusiform cortex and right superior temporal gyrus (Stewart et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Children with APD had increased functional connectivity in the left inferior frontal gyrus (Broca’s area) and left posterior middle temporal gyrus; these regions are implicated in language production and comprehension and lexical and semantic processes (Hagoort, 2014; Acheson et al, 2013; Hickok & Poeppel, 2004). Stewart and colleagues (2021) also reported that in the Semantics network, children with APD had stronger functional connectivity in the right parahippocampal gyrus compared to auditory areas such as left Heschl’s gyrus, left middle temporal gyrus (MTG), right superior temporal gyrus (STG), and right planum temporale. Still, they had weaker connections in the left temporal fusiform cortex and right superior temporal gyrus (Stewart et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…Stewart and colleagues (2021) also reported that in the Semantics network, children with APD had stronger functional connectivity in the right parahippocampal gyrus compared to auditory areas such as left Heschl’s gyrus, left middle temporal gyrus (MTG), right superior temporal gyrus (STG), and right planum temporale. Still, they had weaker connections in the left temporal fusiform cortex and right superior temporal gyrus (Stewart et al, 2021). Stewart et al (2021) concluded that atypical neurological aspects of APD are connected with language comprehension, consistent with the high rate of language disorder comorbidity in children with APD (Sharma et al, 2009; Dawes & Bishop, 2010; Barker et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations